Studies on Extension of Shelf-life of Roselle (Hibiscus sabdariffa) Extract - Abiose, S.H.; Adeniran, H. A. (Ife Journal of Technology, 2010)
The effect of pasteurization and addition of two preservatives (sodium metabisulphite and sodium benzoate) was studied on roselle juice (zobo) with a view to extending its shelf-life. Six samples of six treatments (A-conventional sample, B – pasteurized, C- conventional sample with 500mg/kg sodium benzoate, D conventional sample with 200mg/kg sodium metabisulphite, E – conventional sample with 500mg/kg sodium benzoate and pasteurization and F conventional sample with 200mg/kg metabisulphite with pasteurization) were prepared and stored for six weeks at ambient (28 ± 1 0C) and refrigeration temperatures (5 ± 1 0 C). Physico-chemical (pH, titratable acidity and oBrix) and microbiological analyses of samples were carried out weekly using standard methods. Results showed pH, titratable acidity and oBrix values to range between 2.76 – 2.97, 0.075 - 0.207% and 9.0 - 9.6 respectively while coliform bacteria, yeast/moulds were nil over a period of six weeks. Sodium metabisulphite (200mg/kg) with or without pasteurization at 70 oC effectively preserved the product over the period of storage. These results have established that the shelf-life of roselle juice can be extended to between three and six weeks by pasteurization and addition of sodium metabisulphite (Na2S2O5) or sodium benzoate at 200 or 500mg/kg respectively.